Valdosta State College Football 1984 - Valdosta State University, Athletics Department (Valdosta State University, 1984)
As Valdosta State prepares to enter its third season of football, head coach Jim Goodman sees a defense that has reached the point of competitiveness in the Gulf South Conference and an offense which is still young and inexperienced.
*Valdosta State College Football 1984.* Program. Gulf South NCAA, Division II. Valdosta State University, 1984. ### Staff 1984 Steve Roberts; Jim Berryman; Bobby Johns; Kenneth Hand; Eric Schumann; Ted Suttle; Dick Russell; Calvin Rackley; Norman Sims; Gary Hughes; Danny Hayes; Jim Goodman; Jim Madaleno; ### Players 1984 Jerome Smith; Frank Scantling; Ryan Grubb; Thaddeus Bell; Bill Wilhelm; Jerry Randall; Elson Bolar; Dean Siegel; Andy Sharpless; Ben Reaves; Keith Bonnell; Ken Fasnacht; Chuck Dunmon; Kevin Gray; Mark Lawson; Terry Graham; John Turley; Derryl Mason; Dan Strickland; Wayne Hamm; Kevin Cotton; Cary Cody; Jessie Tuggle; James Gibson; R. D. Swain; Robert Renfro; Don Pumphrey; Keith Reddings; Buddy Ratledge; John Horris; Bryan Banks; Jay Walls; 7FC2236E-FB2C-4278-B4BB-3A91E3212D76
Keywords: Athletics; Football